Consent and compliance: serviceable subjects in involuntary psychiatric commitment hearings in Paris and New York - Barnard, Alex V. (Law & society review, 2025)
How do legal and medical professionals construct patients’ legal status and mental states in courtrooms, and how do patients themselves shape those constructions? This paper analyzes 300 hearings in Paris and New York City where people who have been involuntarily hospitalized in psychiatric facilities ask to be released. In both cities, courts reject the vast majority of requests. They do so by drawing on the two systems’ distinctive legal repertoires and control capacity to make patients into different kinds of serviceable subjects : people whose rights are given nominal consideration in the courtroom, but who are nonetheless classified as needing the forced interventions that the psychiatric system has the resources to provide. In Paris, legal professionals emphasize procedural rights while deferring to medical evaluations of patients’ consent, defined as their underlying willingness to accept long-term treatment. In New York, lawyers challenge psychiatric expertise but bargain with doctors and patients over compliance, understood as a short-term acceptance of medication. This paper reorients attention from the self-governing subjects that hybrid medical-legal-welfare interventions claim to ultimately produce toward the more contingent and situational serviceable subjects that allow for ongoing professional collaboration and institutional processing in contexts of diminished resources and expanded patients’ rights.